The Autism-Spectrum Quotient–Hebrew version: Psychometric properties of a full and a short form, adapted for DSM-5. (April 2023) - Golan, Ofer; Terner, Michael; Israel-Yaacov, Sandra; Allison, Carrie; Baron-Cohen, Simon
The Autism-Spectrum Quotient is a self-report scale, used to assess autistic traits. It was tested cross-culturally, and a short version was created to clinically refer adults for an autism assessment. This study aimed to examine the properties of the Hebrew version of the Autism-Spectrum Quotient and to create a short version suitable for Diagnostic and Statistical Manual of Mental Disorders (5th ed.). Ninety-three clinically diagnosed autistic adults (24 females) aged 18–53, and 147 comparable controls (34 females) completed the Hebrew version of the Autism-Spectrum Quotient. Ten clinicians specializing in diagnosing autism in adults classified the Autism-Spectrum Quotient's items according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria. The Hebrew version of the Autism-Spectrum Quotient showed good internal consistency (Kuder-Richardson 20 = 0.90). Based on the prevalence of autism among clinically referred adults (70%), receiver operating characteristic analysis yielded area under the curve of 0.94. A cutoff of 21 demonstrated high sensitivity (0.90), specificity (0.76), positive predictive value (0.90), and negative predictive value (0.77). The short version of the Hebrew Autism-Spectrum Quotient included five social communication and five restricted, repetitive behavior items, which represented two social communication and two restricted, repetitive behavior criteria of Diagnostic and Statistical Manual of Mental Disorders (5th ed.). It showed good internal consistency (Kuder-Richardson 20 = 0.86), and receiver operating characteristic analysis yielded area under the curve of 0.95. An optimal clinical cutoff of five showed high sensitivity (0.90), specificity (0.82), positive predictive value (0.92), and negative predictive value (0.78). The Hebrew version of the Autism-Spectrum Quotient and the short version of the Hebrew Autism-Spectrum Quotient can be effectively used to help screen for autism in clinically referred adults. Lay Abstract: Despite the attempt to diagnose autism at an early age, there are still many individuals who would only get an autism diagnosis in adulthood. For these adults, a questionnaire that could assist in highlighting their need to seek diagnostic assessment is needed. The Autism-Spectrum Quotient is a self-report scale used to assess autistic traits. It was tested cross-culturally, and a short version was recommended to help identify adults who should be referred for an autism assessment. However, its relevance for the up-to-date diagnostic criteria, according to the Diagnostic and Statistical Manual of Mental Disorders (5th ed.), has not been tested. This study aimed to examine the psychometric properties of the Hebrew version of the Autism-Spectrum Quotient and to create a short version of the Hebrew Autism-Spectrum Quotient, based on items which map on to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria. Ninety-three autistic adults (24 females), aged 18–51, clinically diagnosed according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.), and 147 comparable controls (34 females) filled out the Hebrew version of the Autism-Spectrum Quotient. Ten clinicians who specialize in diagnosing autism in adults classified the Autism-Spectrum Quotient's items according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria. The short version of the Hebrew Autism-Spectrum Quotient comprised items that best differentiated between adults with and without autism, five items representing each of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) diagnostic domains. The overall probability for participants to be correctly classified as autistic or neurotypical was 86% for the Hebrew version of the Autism-Spectrum Quotient and 88% for the short version of the Hebrew Autism-Spectrum Quotient. We conclude that both versions are reliable and sensitive instruments that can help referring adults for autism assessment.